Evaluation of bone excision effects on a human skull model - I: Mechanical testing and digital image correlation. - Franceskides, Constantinos; Leger, Thibault; Horsfall, Ian; Tozzi, Gianluca; Gibson, Michael C.; Zioupos, Peter (Sage, 2019)
The mechanisms of skull impact loading may change following surgical interventions such as the removal of bone lesions, but little is known about the consequences in the event of subsequent head trauma. We, therefore, prepared acrylonitrile butadiene styrene human skull models based on clinical computed tomography skull data using a three-dimensional printer. Six replicate physical skull models were tested, three with bone excisions and three without. A drop tower was used to simulate the impact sustained by falling backwards onto the occipital lobe region. The impacts were recorded with a high-speed camera, and the occipital strain response was determined by digital image correlation. Although the hole affected neither the magnitude nor the sequence of the fracture pattern, the digital image correlation analysis highlighted an increase in strain around the excised area (0.45%–16.4% of the principal strain). Our approach provides a novel method that could improve the quality of life for patients on many fronts, including protection against trauma, surgical advice, post-operative care, advice in litigation cases, as well as facilitating general biomechanical research in the area of trauma injuries.
Keywords: Biopsy; bone fracture; strains; digital image correlation; physical models